Functional variants of nouns with the suffix -ush-/-yush- in modern Russian language - E.A. Makleeva (Ученые записки Казанского университета: Серия Гуманитарные науки)
The object of research in this work is derived nouns with the suffix -ush-/-yush- (-уш-/-юш-). The relevance of the study is determined by the fact that this suffix has been insufficiently studied, probably because it is productive mainly in speaking and the number of words with the suffix -ush- in dictionaries is small. The empirical material has been taken from A.A. Zaliznyak's “Grammatical Dictionary of Russian Language”, explanatory dictionaries and the Russian National Corpus; a total of 250 derivative words have been identified and analyzed. Based on the method of complex functional analysis developed by us earlier, the functional properties and the morphemic status of the suffix -ush- were determined. It has been established that this suffix is a word-forming one, five word-formation types of derivative words with the suffix -ush- have been described. They can perform expressive, compressive, stylistic or nominative function in speech. Furthermore, suffixes of all derivational types have been characterized based on the positions of invariance/non-invariance, as well as the presence of a system-forming and functional-stylistic potential and a functional-stylistic orientation. The results of the functional analysis reveal that there are four functional-stylistic variants of the suffix -ush-. The obtained data can be used in teaching Russian and Russian as a foreign language. The study shows that it is possible to create a system-functional catalog of Russian affixes in the future.